Mucosal Vaccination Against Periodontal Disease: Current Status and Opportunities - Vaernewyck, Victor; Arzi, Boaz; Sanders, Niek N.; Cox, Eric; Devriendt, Bert (Frontiers in Immunology, 2021)
Approximately 9 out of 10 adults have some form of periodontal disease, an infection-induced inflammatory disease of the tooth-supporting tissues. The initial form, gingivitis, often remains asymptomatic, but this can evolve into periodontitis, which is typically associated with halitosis, oral pain or discomfort, and tooth loss. Furthermore, periodontitis may contribute to systemic disorders like cardiovascular disease and type 2 diabetes mellitus. Control options remain nonspecific, time-consuming, and costly; largely relying on the removal of dental plaque and calculus by mechanical debridement. However, while dental plaque bacteria trigger periodontal disease, it is the host-specific inflammatory response that acts as main driver of tissue destruction and disease progression. Therefore, periodontal disease control should aim to alter the host’s inflammatory response as well as to reduce the bacterial triggers. Vaccines may provide a potent adjunct to mechanical debridement for periodontal disease prevention and treatment. However, a successful periodontal vaccine should induce protective immunity in the oral cavity, which proves difficult with traditional vaccination methods. Recent advances in mucosal vaccination may bridge the gap in periodontal vaccine development. In this review, we offer a comprehensive overview of mucosal vaccination strategies to induce protective immunity in the oral cavity for periodontal disease control. Furthermore, we highlight the need for additional research with appropriate and clinically relevant animal models, before discussing several opportunities for periodontal vaccine development.